Transactional, transformational, union and organizational commitment: An examination of the effect flaws - Dhammika, K. A.. S.; Ahmad, Fais; Thi, Lip Sam (Center for Promoting Ideas (CPI), USA, 2013)
A vast array of knowledge has been accumulated on leadership and leadership effectiveness in particular with a large number of studies over the past years. However, the effect of leadership of managers on some behavioral aspects of employees that are not in the immediate interest of managers in organizations is relatively unattended by the leadership researchers. The effect of leadership on union commitment of employees is such an issue that has been least attended by researchers.The objective of this study is to examine the effect flaws exist between transactional and transformational leadership, organizational commitment, and union commitment of unionized employees. A sample of 380 employees from the 33 public sector organizations in Sri Lanka was drawn.The parallel model testing procedure based on Structural Equation Modeling (SEM) was used for testing the hypothesized models.The results revealed that transactional and transformational leadership has a direct effect and an indirect effect as well via union commitment on organizational commitment of employees.